Life Cycle Assessment of Solar Panels: Environmental Impacts from Production to Disposal - Avitesh Vaishnavi Nayak; Tejwant Singh Brar (International Journal of Environmental Planning and Development Architecture, 2025)
LCA is a way to evaluate the full environmental impact of something—like a product, material, activity, or building—from start to finish. As solar energy adoption accelerates globally, understanding the full environmental implications of PV technology becomes crucial for informed decision-making and sustainable development. The study employs a cradle-to-grave approach, analyzing the environmental footprint of solar panels across multiple impact categories. These include global warming potential, energy payback time, water consumption, toxicity, and resource depletion. For this study, data has been taken from manufactures and experts of building construction. Results indicate that while solar panels significantly reduce greenhouse gas emissions during their operational phase, the production and disposal stages present notable environmental challenges. The energy-intensive manufacturing process, particularly silicon purification and wafer production, contributes substantially to the overall carbon footprint. The paper concludes by highlighting the need for continued innovation in manufacturing processes, material efficiency, and recycling technologies to further enhance the environmental performance of solar panels. It also emphasizes the importance of developing robust policies and infrastructure for PV waste management to ensure the long-term sustainability of solar energy deployment.
Keywords: Environmental Impacts; Innovation; Life cycle; PV panels; Solar Energy; carbon footprint